On (semi)topology L-algebras - Mona Aaly Kologani (Categories and General Algebraic Structures with Applications, 2023)
Here, we define (semi)topological L-algebras and some related results are approved. Then we deduce conditions that mention an L-algebra to be a semi-topological or a topological L-algebra and we check some attributes of them. Chiefly, we display in an L-algebra L, if (L, ↠, τ ) is a semi-topological L-algebra and {1} is an open set or L is bounded and satisfies the double negation property, then (L,τ) is a topological L-algebra. Finally, we construct a discrete topology on a quotient L-algebra, under suit- able conditions. Also, different kinds of topology such as T0 and Hausdorff are investigated.